2014
DOI: 10.1016/j.iree.2013.10.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of blended courses on student learning: Evidence from introductory economics courses

Abstract: Over the past decade there has been a large increase in the number of colleges and universities that offer fully online courses and blended courses (courses with a face-to-face component and with an online component). The number of students enrolling in these courses has also increased. These courses are less costly for universities to offer and provide students with more flexibility than traditional classes. However, the effect of these courses on student learning remains unclear. This study examines the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Using a difference-in-differences identification strategy, the authors find that the blended format had no effect on students' quiz scores, although the effects were negative for male students and positive for female students. The other quasi-experimental study included in this review, Olitsky and Cosgrove (2014), employs a propensity score matching technique to control for bias stemming from non-random selection into a hybrid delivery format. The authors find that the hybrid section was associated with lower student results in several outcome measures, although these effects are statistically insignificant for nearly all measures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a difference-in-differences identification strategy, the authors find that the blended format had no effect on students' quiz scores, although the effects were negative for male students and positive for female students. The other quasi-experimental study included in this review, Olitsky and Cosgrove (2014), employs a propensity score matching technique to control for bias stemming from non-random selection into a hybrid delivery format. The authors find that the hybrid section was associated with lower student results in several outcome measures, although these effects are statistically insignificant for nearly all measures.…”
Section: Resultsmentioning
confidence: 99%
“…None of the studies included in this literature review examine the effect of delivery formats on course costs, and yet several suggest that the potential cost reductions-or increases-associated with online and hybrid courses may be what ultimately drive the extent to which their results are actionable (Joyce et al (2014), Kwak et al (2015), Olitsky and Cosgrove (2014)). To support action on the ground, the research must address not only the effects of online and hybrid instruction on learning outcomes, but also their efficiency.…”
Section: Avenues For Further Researchmentioning
confidence: 99%
“…6 In one of the strongest studies, Bowen, Chingos, Lack, and Nygren (2014) contrast traditional and hybrid versions of a statistics class in a randomized controlled trial and find no significant differences in learning outcomes, with small standard errors and reason to believe there would be cost savings from widespread use of the hybrid method. Several experimental and quasi-experimental studies have found small negative effects of hybrid versus traditional instruction in various contexts (for example, see Joyce, Crockett, Jaeger, Altindag, and O'Connell 2014, Kwak, Menezes, and Sherwood 2015, and Olitsky and Cosgrove 2014, as reported in Wu 2015.) These findings say little about fully online instruction nor about likely outcomes in courses with different subject matters.…”
Section: Changes In Student Outcomes and Pedagogymentioning
confidence: 96%
“…However, neither study controlled for selection bias by mode. Olitsky and Cosgrove () compared learning outcomes in blended and web‐enhanced classes. After controlling for selection bias using propensity score matching, no significant difference in outcomes between the blended and web‐enhanced classes persisted.…”
Section: Literature Reviewmentioning
confidence: 99%